High rate of mortality in Spanish community‐dwelling population aged 85 with atrial fibrillation after three years of follow‐up: The Octabaix study1. (15th March 2016) - Formiga, Francesc; Ferrer, Assumpta; Mestre, Delia; Brasé, Ariadna; Soldevila, Laura; Corbella, Xavier
Abstract : Aim: To assess the possible association between three‐year global mortality and atrial fibrillation (AF) in 328 community‐dwelling participants aged 85 at baseline. Methods: Sociodemographic data, comorbidity and geriatric assessment tools, thromboembolic risk, and AF therapy were assessed. We compared the patients who survived with those who died. Results: At baseline, 41 (12.5%) of participants had permanent AF, and 13 of them died (31.7%) after the three‐year follow‐up period compared with 44 (15.3%) of the rest of cohort ( P = 0.01). Cox regression analysis identified two significant clinical variables as independent predictors of three‐year risk of global mortality: Lawton Index (hazard ratio 0.82, 95% confidence interval 0.75–0.91) and AF (hazard ratio 1.90, 95% confidence interval 1.01–3.56). None of the other of variables evaluated showed predictive value of global mortality in the AF patients. Conclusion: In oldest old community‐dwelling participants, AF is an independent risk factor for global mortality after a three‐year follow‐up period.